Awareness and Practices on Handwashing and the Use of Mask Among Non-Allied Health Students: A Basis for Health Promotion - Martinez, Allyssa Cheleth; Rhone Jr., Rudolph F.; Caagbay, Raymond C. (8ISC Proceedings: Covid-19, 2022)
The use of masks for the protection against COVID-19 infections has been very common in the year 2020. However, there is little to no literature regarding this concept. The aim of the study was to identify the level of awareness and practices in the use of masks and as well as to determine if the relationship exists between the variables. A descriptive-evaluative, descriptive-comparative, and descriptive- correlational research design was used in this study. One hundred non-allied health students were chosen to participate in this study using the purposive sampling technique. The results revealed that awareness of the respondents on handwashing and its use is high. It also shows that there is a high level of practice on handwashing and the use of masks. The respondents’ perception of the use of masks and handwashing practices showed a significant positive relationship between the awareness of the use of masks and practice on handwashing. There was no significant difference found in the level of awareness and practices on handwashing when grouped according to sex, year level, colleges, and family income. However, a significant difference was found in the awareness level when grouped according to age and also in practices on the use of masks when grouped according to sex and the college they belong to. Keywords : awareness, practices, mask, handwashing, health promotion